2004
DOI: 10.1111/j.1479-828x.2004.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of mid luteal progesterone concentration before luteal support in controlled ovarian hyperstimulation with intrauterine insemination

Abstract: Increased mid luteal serum P4 levels are not associated with a higher CPR in women undergoing COH with IUI. However, a low mid luteal P4 level < or =25 nmol/L may help predict treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…With regard to the significance of midluteal level of P 4 , it was reported that luteal P 4 level in stimulated cycles does not predict cycle outcome (27) and that even too much P 4 may be somewhat detrimental (28). In concordance with this finding our data regarding serum P 4 agrees with this conclusion where study group III (P 4 plus hCG) had the highest serum P 4 level followed by group I and then group II, which had the lowest serum P 4 .…”
Section: Discussionmentioning
confidence: 98%
“…With regard to the significance of midluteal level of P 4 , it was reported that luteal P 4 level in stimulated cycles does not predict cycle outcome (27) and that even too much P 4 may be somewhat detrimental (28). In concordance with this finding our data regarding serum P 4 agrees with this conclusion where study group III (P 4 plus hCG) had the highest serum P 4 level followed by group I and then group II, which had the lowest serum P 4 .…”
Section: Discussionmentioning
confidence: 98%
“…In IUI, a low midluteal P level has been described as a predictor of treatment failure (33). It is assumed that the luteal-phase deficiency and the luteolytic effect of the GnRH agonist (2,11,34,35) are overcome by P administration in the luteal phase of ART cycles (30).…”
Section: Discussionmentioning
confidence: 99%
“…As well as, Ebrahimi and colleagues in a clinical trial concluded that the progesterone suppositories does not effect on improving IUI treatment [12]. In a retrospective study by Costello in 2004, they published no positive significant relation between the luteal phase support by progesterone in IUI cycles and increasing pregnancy rate [13]. Enumeration data presented as N (%) with P-value obtained from chi-square or fisher exact tests.…”
Section: Discussionmentioning
confidence: 99%